Methodology of Teaching the Subject of Parameter Repetition Operator (In the example of the Python programming language) - Kamalova Nilufar Ilxomovna (Genius Journals, 2022)
The article outlines methods of teaching a parameter repeat operator in teaching programming languages based on interfaith methods in the example of python programming language
Keywords: Generation Z; interactive methods; programming language; python